Do emotional strategies work? Evidence from rumor clarification announcement - Ji, Peinan; Ji, Hui; Guo, Linke; Yang, Xiaojuan; Han, Yang (Journal of Business Economics and Management, 2025)
Financial markets are filled with rumors because of information asymmetry. Although issuing clarification announcements is the most straightforward approach for organizations, previous research has mostly focused on analyzing the influence of rumors and the heterogeneity of their clarification statements on the efficacy of rumor management. This study investigates how mood elements influence the effectiveness of 335 rumor clarification statements in China’s A-share market from 2019 to 2023. By employing textual sentiment analysis, event study method, and fixed-effects regression models, the primary results indicate that rumors vary in their characteristics and have diverse effects on stock price volatility. Furthermore, we find that clarification announcements effectively restore stock values, though their influence on negative rumors is somewhat restricted. Announcements with a positive mood greatly improve the effectiveness of clarification, particularly when addressing favorable rumors. The level of transparency and the characteristics of the firm’s information influence the impact of sentiment. Furthermore, the positive impact of sentiment is more noticeable in firms that are extremely transparent or not owned by the state.